C-14 Release Behavior and Chemical Species from Irradiated Hull Waste under Geological Disposal Conditions. Issue 1665 (2014) - Yamashita, Yu; Tanabe, Hiromi; Sakuragi, Tomofumi; Takahashi, Ryota; Sasoh, Michitaka
ABSTRACT: C-14 contained in Hull waste is one of the most important radionuclides in the safety assessment of transuranic (TRU) waste disposal. For more realistic safety assessment, it is important to clarify the release mechanism and chemical species of C-14 from Hull waste. In this research, leaching tests were conducted using an irradiated Zry cladding tube from a boiling-water reactor (BWR) to obtain leaching data and to investigate the relationship between Zry metal corrosion and C-14 release behavior. Both organic and inorganic C-14 compounds existed in the the liquid phase, and some C-14 moved to the gaseous phase. The release rate of C-14 obtained from the BWR cladding tube after two-year leaching tests was lower than the release rate from a pressurize water reactor (PWR) cladding tube. It is considered that the BWR cladding tube used in this test did not easily corrode since it used a comparatively new material. The release rate of C-14 was slightly lower as compared with the corrosion rate of unirradiated Zry. This is thought to be the result of improved corrosion resistance conferred by neutron irradiation, which encouraged the dissolution of grain boundary precipitation elements, such as Fe, Cr, and Ni, into the crystal grains. The leaching tests will be continued for 10 years.